Essential oil supplementation improves insulin sensitivity and modulates the plasma metabolome of hyperinsulinemic horses - Loos, Caroline M. M.; Zhao, Shuang; Li, Liang; Li, Janet; Han, Wei; Vanzant, Eric S.; McLeod, Kyle R. (Frontiers in Veterinary Science, 2024)
The objective of this study was to investigate the effect of essential oil (EO) supplementation on insulin sensitivity (IS) and the plasma metabolome in insulin dysregulated (ID) horses. Horses were blocked by degree of IS and assigned randomly to treatment: oral daily bolus (50 mL) of either a plant derived EO supplement or carrier (CON). Mares were housed in dry lots with ad libitum access to grass hay and supplemented individually twice daily with a concentrate to meet nutrient requirements for mature horses. Before and after 6 wks of treatment, mares underwent a combined glucose-insulin tolerance test (CGIT) and an oral sugar test (OST) on separate days. Global metabolome analysis was conducted on plasma samples before and after treatment. Although treatment did not affect (p > 0.4) AUC or glucose clearance during CGIT, there was a treatment*covariate interaction (p ≤ 0.08) for insulin concentrations at 75 min (INS75) and positive phase time (PT) with EO decreasing both INS75 (p ≤ 0.002) and PT (p = 0.05) in horses with more severe initial degree of ID. Similarly, EO treatment reduced (p ≤ 0.006) insulinemic response to the OST in horses exhibiting higher pre-treatment responses (treatment*covariate, p = 0.004). There were 702 metabolites identified that were uniquely changed with EO treatment. Pathway analysis and biomarkers showed EO-mediated changes in amino acid, linoleic acid, mesaconic acid, TCA-cyle intermediates and bile acid metabolism. The directional changes in these pathways or biomarkers are consistent with changes in inulin sensitivity in other models. These data show that EO shifted the plasma metabolome and improved insulin sensitivity in horses.